Implementation Of The Regional Financial Management Information System On The Quality Of Financial Reports (Study on the Regional Asset and Financial Management Agency of the City of Palopo) - Lisdamayanti; Muhammad Aqsa; M. Risal (Institute of Computer Science (IOCS), 2022)
Financial management in local governments has utilized technology as a basis in an information system. One of them is the development of the Regional Management Information System application to facilitate financial management in local governments so that it will produce good quality financial reports. This study aims to analyze the effect of the application of the Regional Financial Management Information System on the quality of financial reports produced at the Regional Financial and Asset Management Agency of Palopo City. This research is an explanatory quantitative research where the population is all employees at the Regional Financial and Asset Management Agency of Palopo City with saturated sampling technique so that the total population is used as respondents as many as 107 respondents. The data was collected through the distribution of questionnaires where before distributing the questionnaires, validity and reliability tests were carried out. The data that has been collected will be analyzed descriptively and verified by using the SPSS statistical tool . The results showed that the Regional Financial Management Information System had a significant effect on the quality of financial reports at the Regional Financial and Asset Management Agency of Palopo City.